Hybrid Working, Well-being and Gender: A Study on a Public SectorOrganization During the COVID-19 Pandemic (Asian Journal of Social Science Studies, 2023)
During the COVID-19 global pandemic, likewise private sector, public sector organisations also shifted to partial homeworking or hybrid working to comply with the government-imposed social distancing policies. This study examines the effect of enforced hybrid working on employee well-being via markers of stress, workload, loneliness, and detachment. This study also investigates the impact of involuntary hybrid working on the gender division of labour. This study applies qualitative research within a cross-sectional design to identify the well-being outcomes and experiences of male and female employees. The findings of this study reveal that factors such as disruptions in internet connectivity, increased workload, longer working hours with no fixed schedule, and lack of interaction with colleagues and social support negatively affect well-being leading to increased stress while working from home. Family responsibilities including child caring while working from home influence female employees‟ well-being. In addition, hybrid working provides advantages of both onsite and homeworking and thus, provides an opportunity to balance work and family life.